The effect of virtual laboratory implementation (Proxmox) on students' cognitive and psychomotor learning outcomes - Yarliansyah Agustian; Hansi Effendi; Yasdinul Huda; Rijal Abdullah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aims to examine the effect of implementing a Proxmox Virtual Environment–based virtual laboratory on students’ cognitive and psychomotor learning outcomes in Computer and Network Engineering, addressing limited physical server availability at SMK Negeri 1 Batam. A quasi-experimental Nonequivalent Control Group Design was employed involving 59 students selected through purposive sampling. Cognitive outcomes were measured using a validated 40-item test (KR-20 reliability), while psychomotor skills were assessed using a performance rubric with inter-rater reliability (Cohen’s Kappa). Data were analyzed using Independent Sample t-test and N-Gain, preceded by normality and homogeneity tests. The experimental group showed significantly higher outcomes than the control group (p < 0.05). Cognitive N-Gain reached 82.68% (high), compared to 70.30% in the control group. Psychomotor N-Gain was 83.48%, exceeding the control group’s 76.97%, indicating more consistent technical performance. Proxmox-based virtual laboratories are effective in enhancing learning outcomes and provide a scalable solution for vocational education with limited infrastructure.